the Internal mechanism of correlation between angiotensin II gene and serum adiponectin level in patients with cerebrovascular complications of H-type hypertension: Internal Mechanism of Cerebrovascular Complications of H-type Hypertension - Wen, Shangyu (Journal of Medical Biochemistry, 2024)
Abstract: It was to explore the correlation between angiotensin II (Ang II) gene and serum adiponectin expression in patients with cerebrovascular complications of H-type hypertension (HH) and its mechanism. A total of 50 cases of outpatient patients in Tianjin Fourth Central Hospital were recruited from January 2022 to June 2023 and rolled into three groups according to their blood pressure and basic information, namely HH cerebrovascular complications group, the non-H-type hypertension (NHH) group, and the healthy control (HC)group. Peripheral blood samples were taken, one sample was utilized to test for the Ang II gene and the methylation of Ang II, and the other sample was utilized to measure serum adiponectin levels, so as to analyze the relationship between serum adiponectin level and Ang II in patients with cerebrovascular complications of HH. The ratio of male to female was 8:7 in the group of cerebrovascular complications of HH, and mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 167.34mmHg and 112.56mmHg, respectively. In NHH group, the mean SBP was 165.89mmHg and the mean DBP was 113.47mmHg. The blood pressure of HC group was in the normal range. The Ang II content was the highest in the group with cerebrovascular complications of HH, followed by the group with NHH, and the lowest in HC group. Pyrosequencing chart of patients with cerebrovascular complications of HH showed that the content of deoxyphosphate ribose G was the highest, while the content of A was the highest in NHH patients. Moreover, the serum adiponectin level of patients with HH and NHH was superior to that of HC group, and adiponectin level between the former two groups and HC groupdiffered considerably. Ang II levels were high in patients with cerebrovascular complications of HH and were positively correlated with adiponectin levels. The incidence of cerebrovascular complications of HH may be related to Ang II level in patients.